Neuroendoscopic Management of Intraventricular Germinoma at the Foramen of Monro: Case Report and Review of the Literature - Yip, C.-M.; Hsu, S.-S.; Liao, W.-C.; Chen, J.-Y.; Liu, S.-H.; Chen, C.-H. (min - Minimally Invasive Neurosurgery, 2011)
Intraventricular tumors account for approximately 3% of adult brain tumors and 16% of childhood and adolescent brain tumors. Half of the intraventricular tumors in adults and one quarter of those in children are found in the lateral ventricles. Ependymoma, astrocytoma, oligodendroglioma, choroid plexus papilloma, meningioma and subependymal giant cell astrocytoma are the common tumors encountered at this particular site. A germinoma at this site is rare. Microsurgery of intraventricular tumors can be challenging and is performed with potential functional and cognitive complications.A 25-year-old female harboring an intraventricular tumor at the foramen of Monro with resultant obstructive hydrocephalus underwent a right intraventricular endoscopic resection of the tumor by means of frameless neuronavigation guidance and temporary external ventricular drainage. Histology showed the tumor to be a germinoma. The post-operative imaging showed that there was some residual tumor tissue in the fornix. Concerned with possibility of cerebrospinal fluid seeding, we administered postoperative adjuvant craniospinal irradiation. The patient was discharged with a Glascow outcome scale score of 5 and at last the 6-month follow-up there was no evidence of recurrence.This report suggests that in selected cases endoscopic resection of an intraventricular tumor under frameless neuronavigation guidance is feasible and safe. The target can be precisely located and procedure-related adverse events can be minimized.
Keywords: endoscopic resection; frameless neuronavigation; germinoma; intraventricular tumor